Nomadic pastoralists and sedentary farmers of the Sahel/Savannah Belt of Africa in the light of geometric morphometrics based on facial portraits. Issue 4 (29th April 2019) - Kleisner, Karel; Pokorný, Šimon; Čížková, Martina; Froment, Alain; Černý, Viktor
Abstract: Objectives: The Sahel/Savannah belt is a region where two sympatric human subsistence strategies—nomadic pastoralism and sedentary farming—have been coexisting for millennia. While earlier studies focused on estimating population differentiation and genetic structure of this ecologically remarkable region's inhabitants, less effort has been expended on understanding the morphological variation among local populations. Materials and methods: To fill this gap, we used geometric morphometrics to analyze the facial features of three groups of pastoralists and three groups of sedentary farmers belonging to three language families (Niger‐Congo, Nilo‐Saharan, and Afro‐Asiatic) whose mitochondrial DNA sequences have been published previously. Results: Our results show that pastoralists differ from farmers with several facial features. We also found that individuals who bear maternally inherited haplotypes of Eurasian ancestry do not significantly morphologically differ from individuals whose maternal ancestry is sub‐Saharan. Conclusions: Our study follows up and builds upon population genetic and phylogeographic studies of Eurasian haplogroups in the Fulani pastoralists and sub‐Saharan haplogroups in the Arab pastoralists, as well as studies on the spread of lactase persistence mutations and other genetic markers. Our results suggest that recent gene flows across the Sahel/Savannah belt were not strong enough to erase a genetic structure established by Paleolithic foragers and further shaped by the adoption of agropastoral food‐producing strategies.